2016
DOI: 10.1038/srep30022
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Detection of Single Living Bacteria via Electrochemical Collision Event

Abstract: We detected single living bacterial cells on ultramicroelectrode (UME) using a single-particle collision method and optical microscopic methods. The number of collision events involving the bacterial cells indicated in current-time (i-t) curves corresponds to the number of bacterial cells (i.e., Escherichia coli) on the UME surface, as observed visually. Simulations were performed to determine the theoretical current response (75 pA) and frequency (0.47 pM−1 s−1) of single Escherichia coli collisions. The expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 25 publications
2
77
0
Order By: Relevance
“…Electrochemical discrete collisions at an ultramicroelectrode (UME) is a useful technique to detect one at a time single biological entities such as cells, [1][2][3] bacteria, [4][5][6][7] macromolecules, 8 viruses, [9][10][11] and synthetic or biological vesicles. [12][13][14][15] Especially, electrochemical detection of single liposome collisions by recording electron transfer from the UME to an encapsulated redox species is fully appropriate for studying their membrane permeability.…”
Section: /19mentioning
confidence: 99%
“…Electrochemical discrete collisions at an ultramicroelectrode (UME) is a useful technique to detect one at a time single biological entities such as cells, [1][2][3] bacteria, [4][5][6][7] macromolecules, 8 viruses, [9][10][11] and synthetic or biological vesicles. [12][13][14][15] Especially, electrochemical detection of single liposome collisions by recording electron transfer from the UME to an encapsulated redox species is fully appropriate for studying their membrane permeability.…”
Section: /19mentioning
confidence: 99%
“…The detection of the nanoimpact is performed using the change in diffusion current. Lee et al [90] has reported a fast electrochemical label-free approach through current blockages caused by collision events for E. coli single cell detection on an ultramicroelectrode. The ferrocyanide-ferricyanide redox couple was used in this study.…”
Section: Nanoimpact Methodsmentioning
confidence: 99%
“…The ferrocyanide-ferricyanide redox couple was used in this study. This methodology has the capability to be used to study other pathogenic bacteria and different target molecules [90]. The problem with the surface blockage detection strategy is the lack of selectivity between various bacterial species and dead and alive cells.…”
Section: Nanoimpact Methodsmentioning
confidence: 99%
“…A second work from the same authors proposed an improved strategy where the signal was enzymatically amplified through the detection of the specific collision of a single virus on a Pt electrode with the aid of a glucose oxidase (GOx)-functionalised specific antibody [265]. Similar approaches were employed using the blocking of the electrode surface to detect other electrochemically inactive single (bio)entities such as bacteria [266,267], proteins and DNA [240].…”
Section: Nanoimpactsmentioning
confidence: 99%